Kan man med hjälp av en ”prova på”-dag öka intresset för naturbruksgymnasiet - skog? - Andersson, Jonas (2017)
The purpose of this study is to see if a tryout day can increase the interest and the number of students applying for the forestry gymnasium. To days situation is that there is a huge lack of people that wants to work with forestry today. And that could be seen on the apply numbers for the forestry gymnasium. Inviting two schools to a tryout day at the forestry gymnasium in Ljusdal has made the study. Two surveys have been made, one before and after the tryout day. The result says that the interest for forestry has increase from a 3,5 to a 4.2 and 75 % of the students that participated in the study said they could think about applying for the forestry gymnasium when the time comes.